THE PRESENCE OF MARRIAGE AND EXTRAMARRIAGE RELATIONSHIPS IN YOUNG FAMILIES (International Congress on Economics, Management and Business Studies, 2026)
Young families represent a socially and psychologically sensitive stage of marital development characterized by identity formation, role negotiation, economic adjustment, and emotional bonding. During this transitional phase, vulnerability to relational instability—including extramarital involvement—may increase. The present study examines the presence and socio-psychological implications of extramarital relationships in young families (marriage duration 1–10 years). Using a cross-sectional quantitative design, data were collected from 284 married individuals aged 22–35. Statistical analyses included descriptive statistics, Pearson correlations, independent t-tests, and multiple regression analysis. Results indicate that 34.5% of participants reported emotional or physical extramarital involvement within the first decade of marriage. Significant negative associations were found between extramarital involvement and marital satisfaction (r = −0.68, p < 0.001), emotional intimacy (r = −0.64, p < 0.001), and trust (r = −0.72, p < 0.001). Psychological distress was significantly higher among affected spouses. Regression modeling revealed that communication breakdown, unmet emotional needs, and digital media exposure significantly predicted extramarital risk (R² = 0.59). The findings underscore the need for preventive counseling programs targeting young couples.
Keywords: Young families, marriage stability, extramarital relationships, marital satisfaction, psychological distress, communication breakdown